SOCIAL MEDIA AS AN ADVOCATE FOR SOCIAL JUSTICE IN NIGERIA: AN APPRAISAL OF FACEBOOK USERS IN EKITI STATE - Awosenusi Omolara Christianah; Awofadeju Peter Olayinka; Babatola Deborah Bukunmi (International Studies Journal)
This study examined social media as an Advocate for Social Justice in Nigeria: An Appraisal of Facebook Users in Ekiti State. However, it also ascertained the level at which the Facebook Users in Ekiti state make use of social media for social justice. This paper employed Media Dependency Theory (MDT). Moreover, this study adopted survey design method and three local government areas each from the three senatorial districts in Ekiti state was stratified, and were randomly selected. The population for the selected local government is 894,254. However, the study considered 400 participants which make up the sample size and this was arrived at through Taro Yamane's formula. The findings of this study revealed that, social media serve as advocate for social justice in Nigeria, also, social media played major role as it serves as platform for the campaign against injustice in Nigeria. It also concludes that, social media influencer project issues related to social justice advocacy campaign, social issue and comic skit. Finally, the study recommends that, the general public should give much preference to social media advocacy campaign on injustice as it helps them to share their opinions on such issues in the society. It also recommends that government agency in-charge of social media regulation should regulate social media in order to curb deception in the social media report on issues related to injustice in Nigeria.